2019
DOI: 10.1111/1440-1681.13212
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐29c protects against inflammation and apoptosis in Parkinson's disease model in vivo and in vitro by targeting SP1

Abstract: MicroRNAs (miRNAs) have been shown to have complicated implications in the pathogenesis of Parkinson's disease (PD). However, the role of miR‐29c and the underlying mechanism in the development of PD remain not well understood. In this work, the MPTP‐treated mice or MPP+‐intoxicated SH‐SY5Y cells were established as an in vivo or in vitro PD model. Then the specific agomir of miR‐29c was employed to examine its biological function on PD progress. We found that miR‐29c was down‐expressed but SP1 was high‐expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…Our previous study suggested that the decreased expression of miR‐29c in PD models exhibited protective effects for neuronal injury (Wang, Yang, et al, 2019). Thus, this present work was set out to investigate the role of miR‐29c in microglial activation and inflammation.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Our previous study suggested that the decreased expression of miR‐29c in PD models exhibited protective effects for neuronal injury (Wang, Yang, et al, 2019). Thus, this present work was set out to investigate the role of miR‐29c in microglial activation and inflammation.…”
Section: Resultsmentioning
confidence: 97%
“…The intracerebral or systemic injection of LPS can induce microglial activation, dopaminergic neuron death and pro‐inflammatory factor secretion (Huang et al, 2017; Qin et al, 2007), which is commonly used to establish a PD model. Our previous study showed that the decreased expression of miR‐29c suppressed the inflammation in MPP + ‐induced SH‐SY5Y neurons and MPTP‐treated animals (Wang, Yang, et al, 2019). The main features of PD are defined as microglial activation and dopaminergic neuron loss (Kong et al, 2019; Sun et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The miR-29 family members are particularly interesting in this regard, because the expressions of miR-29a and miR-29c are both down-regulated in PD [145]. Further, blood miR-29a is overexpressed in levodopa-treated patients with PD [146] and miR-29c overexpression attenuated dopaminergic neuron loss and α-synuclein accumulation in the SN of PD mice [147]. The targets of the miR-29 family also include PER proteins, although the rhythmicity of the miR-29 family has not been reported yet [21,148].…”
Section: Parkinson's Diseasementioning
confidence: 99%